HYBRID LEARNING DI STAIN MAJENE - Ahmad Ridhai Azis; Burhanuddin (El-FAKHRU, 2022)
This research aims to examine the effectiveness of Hybrid Learning at STAIN Majene in learning Indonesian Language. Hybrid Learning is developed for contemporary education. The learning problem in Covid-19 Pandemic Period are the environment and the learning media that have turned to virtual classes. The environment understood by students is a learning environment that presents lecturers in class, studying along with groups in the room. This contemporary education period present a learning with an independent concept and it is free to learn anywhere and anytime. The research approach was quantitative. The Research design was quasi-experimental. The research population was all the students who are in PAI 4 and PAI 6 semester I (odd) academic year 2020/2021. The data analysis techniques were used the SPSS24 application. The result of research showed that the learning outcomes of students in PAI 4 class following the learning process through Hybrid Learning as much as 89.70% succeed to achieve the average score of the minimum completeness criteria. The learning outcomes of students in PAI 6 as much as 91.68% succeed to achieve the average minimum completeness criteria. The use of Hybrid Learning effectively used in Indonesian language learning at STAIN Majene can be seen from the value of sig.(2-tailed)> 0.05 or 0.000>0.05, meaning that hypothesis 1 (H1) which states that Hybrid Learning is effectively used in learning at the Higher Lecturer level, especially in STAIN Majene. Keywords: effectiveness, hybrid learning, virtual class, Indonesian language